(untitled) (Internet of Things and Edge Computing Journal, 2024)
The deployment of autonomous vehicles (AVs) has increased considerably in recent years. Their increased adoption in various domains and industries underscores the need to ensure their performance and reliability in the long term. Vehicular accidents necessitate the development of emergency response systems (ERS) that are effective, real-time, and reliable. A vigorous ERS promises improved safety, better policymaking, and public safety improvements. As critical AI methods, intelligent systems have shown promise in marshalling the complex structure of vehicular control operations and processing multimodal communication flows. These AI algorithms result in a unique approach to absorb information from various scenarios and develop operations and decision protocols in real-time. Although an emergency for an AV can arise from a vehicular accident, terrorist attack, or natural disaster events, the research proposition here explores the advantages of having an AI-based ERS in an AV to prevent mishaps. The ERS can help return safety levels to normal by evacuating passengers from the AV, coordinating with local emergency aid services to reach the site immediately, delivering real-time AV status information to emergency operations, and accessing optimal avenues for an AV to go in the presence of vegetation blockage and wildfire. The concepts of an AV and the ERS are presented. In the next part, perceptions of a robust AV and its conscientious role for various stakeholders are recognized as international law. This paper is organized as follows. Subsequently, we describe earlier related work, the context of this paper, the creation of the AV, and the aims of the ERS. Finally, the first and second aspects of an EV-ERS are summarized in this essay.